Effect Of Pre-Storage Steam Treatment On Shelf-Life of Kings’ Orange (Citrus Sinensis CV. Nobilis) Fruits During Ambient Storage - Aborisade, Abiola Titilola; FANIYI, Oluwalonimi (International Journal on Food, Agriculture and Natural Resources, 2025)
Fresh fruits are susceptible to fungal rots, but postharvest decay control can be applied by physical, chemical, biological, and cultural techniques. Uninoculated ‘Kings’ orange (Citrus sinensis cv. Nobilis) fruits exposed to steam prior to ambient storage were analyzed for quality. Rot occurrence was between 3.3 and 13.3 % weekly increasing with storage. There was no definite trend especially after the first two weeks though initially higher on the most severely heated fruits. Penicillium digitatum, Lasiodiplodia theobromae and Aspergillus niger were associated with rots. Weekly and cumulative weight losses were highest among fruits that received the mildest heat treatment at 55 ͦ C for 25 minutes. Juice content was higher in steam treated fruits though not statistically significantly. Juice pH was more significantly affected by heating as the more severe heat treatments resulted into less acid in the first two weeks but more, later in storage. Titratable acid content was 0.48 to 0.77. In the fifth week, slightly significant reduction in titratable acid occurred in fruits that were heated at 60 ͦ C for 25 minutes compared with control, but it was more significant in comparison with juice from fruits heated at the lower temperature. There were increases in total soluble solids content with storage but insignificant differences between treatments. These results show that the presently applied steam treatments did not have significant undesirable effect on the fruit juice quality during subsequent ambient storage of fruits.